DETERMINAN DAN KONSEKUENSI INVESTASI LINGKUNGAN: Studi Empiris Pada Perusahaan yang Memperoleh Penilaian PROPER - Paramita, Silvia; Chariri, Anis (Diponegoro Journal of Accounting, 2013)
The aim of this research is to examine the effect of determinant variables (firm size, type of industry, and ownership structure) on the environmental investment and the effect of environmental investment on firm performance as the consequences variable. Environmental investment appraisal using PROPER published by the Ministry of Environment of the Republic of Indonesia and corporate performance measured by ROA. This research used quantitative approach that examined the relationship between variables through hypothesis testing. The sampling method was purposive sampling of 30 public listed companies awarded PROPER during 2009-2011. The data analysis and hypothesis testing techniques used multiple regression analysis. The results indicated that firm size and foreign ownership have a positive effect on environmental investment while profile and institutional ownership negatively affect the investment environment. Supporting the previous research, environmental investment has a positive effect on firm performance. Environmental investment can lead to higher profitability, build an image and reputation, and to increase credibility and legitimacy of the company.